Nilai Ekonomi dan Sebaran Aren (Arenga pinnata) di Desa Bukum dan Desa Suka Maju, Kecamatan Sibolangit - Erickson Purba; Oding Affandi; Liliek Pudji Asmono (Peronema Forestry Science Journal, 2014)
Arenga pinnata is a forest plant that has a lot of advantages but can not be utilized yet completely by the local community. This research conducted in Bukum and Suka Maju village from March to May 2013. This research aimed to determine the distribution and economic value of Arenga pinnata. Sampling was done by purposive sampling technique to select the respondents and to determine the distribution of the Arenga pinnata by plotting at each height class as much as 2 plot using random line. Market price approach technique used to determine the economic values. The results of this research showed that the distribution of Arenga pinnata is obtained and dominant grew at the altitude of 600-800 meters above sea level, while the highest economic value of Arenga pinnata is brown sugar (Rp. 333.600.000/year for 31 farmers) and the lowest economic value is palm wine (Rp 39.360.000/year for 10 farmera). The marketing channels of Arenga pinnata involved Arenga pinnata farmers, brown sugar and palm wine producers, collector agents and consumers.Keywords : Aren, Arenga pinnata, distribution, economic value